1990
DOI: 10.1002/1097-0142(19900301)65:5<1146::aid-cncr2820650519>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

A case of infantile acute monocytic leukemia caused by vertical transmission of the mother's leukemic cells

Abstract: A case of infantile acute monocytic leukemia (AMoL), which was probably transmitted from a pregnant woman with leukemia to her unborn infant, is presented. A woman had AMoL when her third infant was born. This infant, who was a boy, also suffered from AMoL when he was 20 months of age. The infant's leukemic cells had the same cytochemical and immunophenotypic patterns as the mother's leukemic cells. By cytogenetic analysis, the majority of the infant's leukemic marrow cells had the 46,XX karyotype and showed n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
2
2

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(39 citation statements)
references
References 5 publications
(2 reference statements)
0
35
2
2
Order By: Relevance
“…Concerning with congenital leukemia born to a mother with leukemia, three children who developed leukemia after birth, 9 months (Cramblet et al 1958), or 20 months (Osada et al 1990), or 70 days (Nishii et al 1974) have been reported. Rigby et al (1964) demonstrated the passage of quinacrine-labeled maternal white blood cells across the placenta to infant's circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning with congenital leukemia born to a mother with leukemia, three children who developed leukemia after birth, 9 months (Cramblet et al 1958), or 20 months (Osada et al 1990), or 70 days (Nishii et al 1974) have been reported. Rigby et al (1964) demonstrated the passage of quinacrine-labeled maternal white blood cells across the placenta to infant's circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, there is little available information regarding the use of imatinib during pregnancy in humans. Several studies in pregnant women with acute leukemia have suggested that maternal leukemia cells can be transferred to infants (2)(3)(4), and because of the immature immune system in the fetus, maternal tumor cells could have a growth advantage over fetal host cells. The fetus and the mother need to tolerate each other's alloantigens such as noninherited maternal antigens (NIMAs) and inherited paternal antigens during pregnancy (5, 6); exposure of the fetus to NIMAs may induce specific tolerance to maternal alloantigens.…”
Section: Introductionmentioning
confidence: 99%
“…Les cas d'atteinte foetale rapportés après un cancer maternel concernent cinq mélanomes malins [6][7][8][9][10], trois leucémies [11][12][13], deux lymphomes [14,15], deux sarcomes [16,17], deux cancers pulmonaires [18,19] [3]. Parmi ces observations, trois (20 %) n'ont pas été confirmées par l'histologie [6,8,10].…”
Section: éPidémiologieunclassified
“…Une patiente est décédée pendant la grossesse. Les survivantes avaient un carcinome bronchique à petites cellules (rémission complète à six mois [21]), une leucémie aiguë myéloïde (rémis-sion complète à trois ans [13]), une leucémie lymphoïde chronique (rémission complète six ans, [22]), un lymphome T (rémission complète à deux ans, [23]) et un cancer du sein de stade IV (survie non précisée ≥ 6 mois, [24]). …”
Section: éPidémiologieunclassified